Effects of insulin-like growth factors I and II on oestrone sulphatase activity in human breast cancer cell lines. - Hwa, I.A.; Reimann, K.; Lim, P.K.; Lai, L.C. (Spandidos Publications, 1999)
Oestrogens play an important role in the development of breast cancer. A very important source of active oestrogens in the breast is oestrone sulphate which is converted to oestrone by oestrone sulphatase. The aim of this study was to assess the effects of IGF-I and IGF-II on oestrone sulphatase activity in, as well as cell growth of, MCF-7 and MDA-MB-231 human breast cancer cell lines. Cells were grown in supplemented DMEM and treated with varying concentrations of IGFs. At the end of the treatment period, intact cell monolayers were washed and assayed for oestrone sulphatase activity and the number of cell nuclei determined on a Coulter Counter. Oestrone sulphatase activity was significantly stimulated by IGF-I and II at concentrations of 100 ng/ml and 200 ng/ml in MCF-7 cells. IGF-I had no effect on oestrone sulphatase activity in MDA-MB-231 cells over the range of concentrations tested. Significant inhibition of oestrone sulphatase was observed in MDA-MB-231 cells at higher concentrations of IGF-II (50 ng/ml, 100 ng/ml and 200 ng/ml). Both IGF-I and IGF-II at higher concentrations (100 ng/ml and 200 ng/ml) significantly inhibited MCF-7 and stimulated MDA-MB-231 cell growth. Since IGF-I and II have effects on cell growth and oestrone sulphatase activity in breast cancer cell lines they may play a role in the development and progression of human breast cancer.